Answer:
x = 6 and y = -11
Explanation:
Given : System of linear equation
y=−3x+7
x=−2y−16
We have to solve the system of equations using the substitution method.
In substitution method, we substitute the value of one variable in term of other and solve for it.
Consider the given system of linear equation
y = −3x + 7 ...(1)
x = −2y − 16 .....(2)
Substitute, (2) in (1), we get,
y = -3(-2y - 16) + 7
Simplify , we get,
y = 6y + 48 + 7
6y - y = - 55
5y = -55
y = -11
Substitute y = -11 in (2), we get,
x = −2(-11) − 16 = 22 - 16 = 6
thus, x = 6
Thus , x = 6 and y = -11